Lead in soils of Mexico: content, spatial variation, availability for humans - N S Sedov; N A Chernykh; F M Romero; O Zamora-Martínez (RUDN Journal of Ecology and Life Safety, 2012)
The distribution of lead in the soil cover of one of the largest cities in the world - Mexico. A comparative analysis of the content of this metal in soils of different parts of the city and its availability is determined for the human body. Found that lead levels in the city vary in the range of 125-1186 mg/kg, significantly higher than background concentrations. The largest number of elements recorded in the central and southern areas of the city, which is associated with the duration and intensity of traffic load. At the same time these areas are characterized by a high degree of bioavailability of the metal (60 to 100%).